Disease type detection in lung and colon cancer images using the complement approach of inefficient sets - Togacar, Mesut (Pergamon-Elsevier Science Ltd, 2021)
Lung and colon cancers are deadly diseases that can develop simultaneously in organs and adversely affect human life in some special cases. Although the frequency of simultaneous occurrence of these two types of cancer is unlikely, there is a high probability of metastasis between the two organs if not diagnosed early. Traditionally, specialists have to go through a lengthy and complicated process to examine histopathological images and diagnose cancer cases; yet, it is now possible to achieve this process faster with the available technological possibilities. In this study, artificial intelligence-supported model and optimization methods were used to realize the classification of lung and colon cancers' histopathological images. The used dataset has five classes of histopathological images consisting of two colon cancer classes and three lung cancer classes. In the proposed approach, the image classes were trained from scratch with the DarkNet-19 model, which is one of the deep learning models. In the feature set extracted from the DarkNet-19 model, selection of the inefficient features was performed by using Equilibrium and Manta Ray Foraging optimization algorithms. Then, the set containing the inefficient features was distinguished from the rest of the set features, creating an efficient feature set (complementary rule insets). The efficient features obtained by the two used optimization algorithms were combined and classified with the Support Vector Machine (SVM) method. The overall accuracy rate obtained in the classification process was 99.69%. Based on the outcomes of this study, it has been observed that using the complementary method together with some optimization methods improved the classification performance of the dataset.
Keywords: Histopathological images; Complement in sets; Metaheuristic optimization; Deep learning